Peran Penyidik Dalam Menangani Kasus Penipuan Online (Studi Kasus Polres Tanjungbalai) - Hutama Hutabarat, Dany Try; Panjaitan, Adelia Maharani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Online fraud has emerged as a threat in various areas, including in Tanjungbalai City. This research discusses the problem, focusing on the role of Tanjungbalai Police investigators in handling online fraud cases. Key challenges involve the complexity of digital technology, increasingly sophisticated fraud tactics, as well as privacy policies and resource limitations. The research method used is empirical law, where data is analyzed through case studies and interviews. This research emphasizes the importance of increasing technological expertise for investigators to increase their ability to handle criminal acts of online fraud. In addition, the analysis focuses on inter-agency cooperation, with a focus on coordination. The research results show that the disclosure of the online fraud case of the give away scheme in the name of Baim Wong in Tanjung Balai City was based on reports from victims and the public. based on reports from victims and the public. Tanjungbalai Police carried out raids on illegal community activities. The Police (Sabhara) collaborated with Satpol PP in patrolling and controlling activities in residential areas (kos-kosan), obtained evidence which was strongly suspected to be online fraudulent activities carried out by individuals acting in the name of Baim Wong, this evidence was then investigated which then revealed the case online give away fraud in the name of Baim Wong. The obstacle for investigators in providing evidence is the budget to present victims in terms of asking for information from victims who are outside the jurisdiction of the Tanjungbalai City Police.